A Combinatorial Biocatalysis Approach to an Array of Cholic Acid Derivatives - F. Secundo; G. Carrea; S. Joppolo di Ventimiglia; J. S. Dordick; M. De Amici (Biotechnology and Bioengineering, 2003)
A 39-member library of bile acid derivatives was prepared starting from 3a,7a,12a-trihydroxy-5b-cholan-24-oic acid methyl ester using a combinatorial biocatalytic approach. A regioselective oxidation step, catalyzed by hydroxysteroid dehydrogenases, followed by an acylation step with a series of different acyl donors catalyzed by Candida antarctica lipase B, led to the modification of the bile acid scaffold. Each member of the library was obtained in high purity and good yield.